If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1(x + 4) = 7(x + -1) Reorder the terms: 4 + -1(4 + x) = 7(x + -1) 4 + (4 * -1 + x * -1) = 7(x + -1) 4 + (-4 + -1x) = 7(x + -1) Combine like terms: 4 + -4 = 0 0 + -1x = 7(x + -1) -1x = 7(x + -1) Reorder the terms: -1x = 7(-1 + x) -1x = (-1 * 7 + x * 7) -1x = (-7 + 7x) Solving -1x = -7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -1x + -7x = -7 + 7x + -7x Combine like terms: -1x + -7x = -8x -8x = -7 + 7x + -7x Combine like terms: 7x + -7x = 0 -8x = -7 + 0 -8x = -7 Divide each side by '-8'. x = 0.875 Simplifying x = 0.875
| 2y-7/5=25 | | 2.3x^2+0.7x-0.59=0 | | 6a+(7a-2)= | | 2(3x+2)=3-6x | | 14-7a=49 | | n/14=6 | | -x^2+4x=2 | | 39-3x=11+7x | | 4x+6=-48-5x | | 4x+6=48-5x | | 7+10x=16+x | | 7*x=10 | | 3x+241=13x-89 | | (8x-4)+(2x-4)= | | -2*e*6cd= | | -4b*-6b= | | 5x=2+4y | | x+78=1894 | | 5x-3=9+2x | | 11(x+9z)-5(x+9z)= | | (3x+7)-6=12x-(x+4)-(4x+5) | | 38.8x+4=12 | | 3(2x+1)-2(3-2x)=5(x-2) | | 3x+5x=240 | | 3t=3(t^2-2t+2) | | r/8=-7 | | 3/4m=5 | | f(x)=0.5x^2+2x-6 | | 10x^2+17+3=0 | | 3(1+1)=60 | | 5q+10=3q+2 | | 2q+10=2q+18 |